2013
DOI: 10.1002/jgra.50291
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐instrument observations from Svalbard of a traveling convection vortex, electromagnetic ion cyclotron wave burst, and proton precipitation associated with a bow shock instability

Abstract: [1] An isolated burst of 0.35 Hz electromagnetic ion cyclotron (EMIC) waves was observed at four sites on Svalbard from 0947 to 0954 UT 2 January 2011, roughly 1 h after local noon. This burst was associated with one of a series of~50 nT magnetic impulses observed at the northernmost stations of the IMAGE magnetometer array. Hankasalmi SuperDARN radar data showed a west-to-east (antisunward) propagating vortical ionospheric flow in a region of high spectral width~1-2 north of Svalbard, confirming that this mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 92 publications
(156 reference statements)
9
53
0
Order By: Relevance
“…The flow structures propagated westward (indicated by the arrow), seen from the relative timings at different beam directions (beam number increases toward east). Thus, SuperDARN observed a TCV (very similar to that reported by Engebretson et al []) due to a group of magnetosheath pressure pulses. While for other groups of pulses, further flow structures were observed, the data quality and coverage were often poor, and the azimuthal propagation between beam directions was not clear.…”
Section: Ionospheresupporting
confidence: 85%
“…The flow structures propagated westward (indicated by the arrow), seen from the relative timings at different beam directions (beam number increases toward east). Thus, SuperDARN observed a TCV (very similar to that reported by Engebretson et al []) due to a group of magnetosheath pressure pulses. While for other groups of pulses, further flow structures were observed, the data quality and coverage were often poor, and the azimuthal propagation between beam directions was not clear.…”
Section: Ionospheresupporting
confidence: 85%
“…Recent observations from Svalbard reported by Engebretson et al . [] showed both of these additional signatures and in addition reported both satellite and ground‐based observations of precipitating protons in association with the Pc1 waves.…”
Section: Introductionmentioning
confidence: 85%
“…[] and Engebretson et al . [] and hybrid simulations by Omidi et al . [] that bow shock instabilities that are capable of causing transient pressure increases at the dayside magnetopause can occur even in the absence of significant solar wind perturbations.…”
Section: Example Eventsmentioning
confidence: 99%
“…Engebretson et al [2013] have reported the observation of electromagnetic ion cyclotron waves and precipitating energetic protons on closed magnetospheric field lines near the magnetopause during a nearly radial IMF. Engebretson et al [2013] have reported the observation of electromagnetic ion cyclotron waves and precipitating energetic protons on closed magnetospheric field lines near the magnetopause during a nearly radial IMF.…”
Section: Discussionmentioning
confidence: 99%
“…One is the magnetosheath cavities reported by Katırcıoğlu et al [2009] that are associated with drops in density, flow velocity, and magnetic field and enhancements in the flux of energetic ions. In section 4 we discuss the impacts of SHFAs on the magnetopause and how such impacts may result in the generation of ion cyclotron waves and precipitation of energetic protons in the outer magnetosphere as suggested by Engebretson et al [2013]. This paper presents results from our simulations on magnetosheath cavities in section 2 and magnetosheath jets in section 3.…”
Section: Introductionmentioning
confidence: 99%